Detection of Very Virulent Infectious Bursal Disease (IBD) in Chicken in West Java - Putri, Ajeng Fabeana; Winarsongko, Agus; Hoerudin, Heri; sekarmila, Gita; Ahpas, Ahpas; Jaelani, Jejen; Gunawan, Wawan; Dewiyanti, Rina; Pratama, Yuda; Nuradji, Harimurti; Fairusya, Nuha; Ekawasti, Fitrine; Adji, Rahmat Setya; Dharmayanti, NLP Indi; Indriani, Risa; Utomo, Bambang Ngaji; Suryatmiati, Sri (Universitas Syiah Kuala, 2024)
Infectious Bursal Disease (IBD), also known as Gumboro disease, is an acute, highly contagious disease that infects chickens and causes a high mortality rate of up to 100% in young animals. The disease is caused by Infectious Bursal Disease Virus (IBDV) of the genus Avibirnavirus, family Birnaviridae. The disease has been reported in Indonesia since 1976, and management strategies for the disease, such as vaccination, have been applied to prevent and control outbreaks in poultry farms. In this study, we conducted the detection of the disease in chickens from a farm in West Java with a mortality rate of 80%. Chickens showing clinical signs, such as sudden death, anorexia, watery diarrhea, and ruffled feathers, were necropsied, and organ samples, including the bursa Fabricius, brain, and spleen, were collected. The samples were then tested using Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) to confirm the diagnosis of IBD. Positive results were obtained in this study, highlighting the need for improved biosecurity in poultry farms in Indonesia. These results also provided a basis for further research on viral characterization to develop detection kits or vaccines for IBD using local isolates from the field in Indonesia.